2018
DOI: 10.1155/2018/8928706
|View full text |Cite
|
Sign up to set email alerts
|

Myxoid Liposarcoma: Prognostic Factors and Metastatic Pattern in a Series of 148 Patients Treated at a Single Institution

Abstract: Objectives The authors reported a retrospective study on myxoid liposarcomas (MLs), evaluating factors that may influence overall survival (OS), local recurrence-free survival (LRFS), metastasis-free survival (MFS), and analyzing the metastatic pattern. Methods 148 MLs were analyzed. The sites of metastases were investigated. Results Margins (p = 0.002), grading (p = 0,0479), and metastasis (p < 0,0001) were significant risk factors affecting overall survival (OS). Type of presentation (p = 0.0243), grading (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 32 publications
3
62
0
Order By: Relevance
“…Unfortunately, the exact tumor size was not available in our database, necessitating us to use the T -stage to derive tumor size information. For that reason, we used 5 cm as a cut-off point for tumor size, instead of the 10 cm cut-off used in most other studies [ 8 , 10 , 11 , 24 , 25 ]. Even though tumor location is generally considered as a prognostic factor in STSs [ 27 ], and to the best of our knowledge, it has never been reported as a prognostic factor for OS in MLS to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the exact tumor size was not available in our database, necessitating us to use the T -stage to derive tumor size information. For that reason, we used 5 cm as a cut-off point for tumor size, instead of the 10 cm cut-off used in most other studies [ 8 , 10 , 11 , 24 , 25 ]. Even though tumor location is generally considered as a prognostic factor in STSs [ 27 ], and to the best of our knowledge, it has never been reported as a prognostic factor for OS in MLS to date.…”
Section: Discussionmentioning
confidence: 99%
“…MLS is relatively sensitive to radiotherapy (RT) [ 12 , 17 , 18 ] and chemotherapy [ 19 , 20 ], in comparison to other STSs. Local control is achieved in 60–98% of patients [ 4 , 7 , 8 , 11 14 , 18 , 21 23 ], resulting in favorable 5-year overall survival (OS) rates of 67–90% [ 5 , 9 , 11 13 , 21 , 23 25 ].Although sample sizes in most of the previous studies are small due to the rarity of the disease, several prognostic factors in MLS have been identified. Age at diagnosis >45years, tumor size >10 cm, presence of >5% round cell component, and positive resection margins are associated with worse (disease-specific) survival [ 5 , 7 , 8 , 11 , 13 , 21 , 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with MLS tend to have metastases to extrapulmonary sites, such as retroperitoneum, abdominal wall, abdominal cavity, and bone, even in the absence of pulmonary metastases [2,7]. Although several authors have reported a high proportion of extrapulmonary metastases of MLS, ranging from 50-78% of all metastases [7][8][9][10], cardiac metastasis is extremely rare. Here we present a case of cardiac metastasis that occurred in a patient with primary MLS of the thigh.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with MLS tend to have metastases to extrapulmonary sites, such as retroperitoneum, abdominal wall, abdominal cavity, and bone, even in the absence of pulmonary metastases [2,7]. Although several authors have reported a high proportion of extrapulmonary metastases of MLS, ranging from 50 to 78% of all metastases [7][8][9][10], cardiac metastasis is extremely rare. Here we present a case of cardiac metastasis that occurred in a patient with primary MLS of the thigh.…”
Section: Introductionmentioning
confidence: 99%